Occurrence of ESBL, AmpC-ESBL, and Carbapenemase Producer Organisms in Clinical Specimens: An Observational Prospective Study - Rajal Dave; Abhijeet Joshi (Journal of Pure and Applied Microbiology)
Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae are the most common Gram-negative bacillus (GNB) isolates from clinical samples. These bacteria produce enzymes such as ESBL, AmpC β-lactamase, and carbapenemase as a resistance mechanism. Enzymes are responsible for resistance development across all cephalosporin and carbapenem antibiotic generations. In this study, we aimed to determine ESBL, AmpC-ESBL, and carbapenemase producer occurrences from clinical specimens from December 1, 2023, to February 1, 2024. We processed the clinical specimens in the Department of Bacteriology, Gurukrupa Laboratory, Pune, and performed the antibiotic susceptibility testing using an automated phenotypic method to identify organisms and their susceptibility profiles for screening ESBL, AmpC-ESBL, and carbapenemase producer organisms by an automated BD phoenix system. Carbapenemase producer organisms were reconfirmed by a modified carbapenemase inactivation method per CLSI guidelines, with 288 GNB strains isolated from 801 clinical specimens. Among all isolates, E. coli, P. aeruginosa, and K. pneumoniae (n = 90) exhibited high levels of drug resistance with a Multiple Antibiotic Resistance Index above 0.80. Therefore, these three organisms were considered for further characterization. P. aeruginosa was the highest ESBL producer at 27.7%, while the highest AmpC-ESBL coproduction was observed in E. coli, with 73.9%, the majority of which originated from urine. The highest Class B and D carbapenemase production was observed at 47.8% and 26.5% in E. coli and K. pneumoniae, respectively. We detected the highest correlation between AmpC and carbapenemase with a 0.81 correlation coefficient. Amikacin displayed good sensitivity among all antibiotics. The high occurrence of AmpC-ESBL producers and carbapenemase production from clinical samples indicates a need for strict antimicrobial policy and interventions. Carbapenem and colistin combination exhibited promising efficacy. Finally, several emerging therapeutic approaches could provide potential solutions for antibiotic use.